ROLE OF DIGITAL PAYMENTS IN DRIVING ECONOMIC GROWTH IN CHENNAI - K. Sivasubramaniyan; Raman, M. Teeka; G. Surendar (International Journal of Engineering Technologies and Management Research, 2025)
In technologically advancing world, financial transactions in many fold and in several aspects need to be done fast. For this purpose, digital payments come into rescue and helps eliminating the need for physical cash. With rapid advancements in technology, digital payments have become the backbone of modern economies. In India, Tamil Nadu has emerged as a leading state for digital payments. To examine the role of digital payments in enhancing Chennai’s economic growth, the study adopted descriptive and causal research design. Primary data from 50 consumers and business people in Chennai were collected through questionnaire. The study suggests, a majority of respondents view digital payments positively interact economic growth. Nearly half the respondents trust digital payments, while a significant portion remains unsure, highlighting the importance of improving security features and user confidence in digital payments. The study suggests a strong consensus that digital platforms significantly contribute in connecting urban and rural economic activities, facilitating more inclusive growth in Chennai's outskirts, and payments are becoming increasingly popular among street vendors and small merchants. The UPIs are expected to play a crucial role in shaping the future of digital payments in Chennai, with mobile wallets and contactless payments also contributing to this trend. In sum, the research findings highlight a strong preference for digital payments in Chennai.